The prevalence of and factors associated with urinary cotinine-verified smoking in Korean adults: The 2008-2011 Korea National Health and Nutrition Examination Survey. - Jae Won Hong; Jung Hyun Noh; Dong-Jun Kim (PLoS ONE, 2018)
BACKGROUND:Smoking rate based on self-reporting questionnaire might be underestimated. Cotinine is the principal metabolite of nicotine and is considered an accurate biomarker of exposure to cigarette smoke. OBJECTIVES:This study evaluated the prevalence of and factors associated with urinary cotinine-verified smoking in Korean adults. METHODS:We analyzed data from 12,110 adults in the 2008-2011 Korea National Health and Nutrition Examination Survey (KNHANES), using three threshold levels of urinary cotinine ≥100ng/ml, ≥50ng/ml, and ≥30ng/ml. RESULTS:The weighted prevalence of urinary cotinine levels of ≥100, ≥50, and ≥30 ng/mL in the whole study population was 34.7%, 37.1%, and 41.1%, respectively. Male sex, younger age, elementary school graduation, household income in the ≤24th percentile, service and sales workers and assembly workers, and high-risk alcohol drinking were associated with a higher prevalence of urinary cotinine level of ≥ 50 or 30 ng/mL, after we adjusted for age, sex, education level, number of family members, household income, occupation, and alcohol drinking. Logistic regression analyses were performed using the aforementioned variables as covariates to identify factors independently associated with cotinine-verified smoking. Men had a higher risk than women of having a urinary cotinine level of ≥50 ng/mL (OR 4.67, 95% CI 4.09-5.32, p < 0.001). When subjects ages 19-29 years were used as controls, adults ages 30-39 years had a 1.19-fold (CI 1.02-1.39, p = 0.026) higher risk of having a urinary cotinine level of ≥50 ng/mL. College graduates had a 32% lower risk of having a urinary cotinine level of ≥50 ng/mL than elementary school graduates (p < 0.001). A household income in the 25-49th percentile (OR 0.82, 95% CI 0.69-0.98, p = 0.026), 50-74th percentile (OR 0.64, 95% CI 0.53-0.76, p < 0.001), or ≥75th percentile (OR 0.64, 95% CI 0.53-0.77, p < 0.001) was associated with a lower risk of having a urinary cotinine level of ≥50 ng/mL compared to a household income in the ≤24th percentile. High-risk (OR 2.75, 95% CI 2.37-3.18, p < 0.001) and intermediate-risk (OR 2.04, 95% CI 1.82-2.30, p < 0.001) alcohol drinking were associated with having a urinary cotinine level of ≥50 ng/mL compared to low-risk alcohol drinking. Similar to the results of the logistic regression analyses of urinary cotinine ≥50 ng/mL, male sex, younger age, elementary school education, household income in the ≤24th percentile, and high-risk alcohol drinking were significantly associated with having a urinary cotinine level of ≥30 ng/mL. Service and sales workers (OR 1.22, 95% CI 1.01-1.48, p = 0.041) had a significantly higher risk of having a urinary cotinine level of ≥30 ng/mL. CONCLUSIONS:Based on a threshold urinary cotinine level of 50 ng/mL, the prevalence of cotinine-verified smoking in a representative sample of Korean adults was 37.1% (men 52.7%, women 15.4%). Younger age, male sex, low education level, service and sales workers, low household income, and high-risk alcohol drinking were associated with the risk of smoking.